2017
DOI: 10.1002/pld3.9
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone inhibitor treatments phenocopy brassinosteroid–gibberellin dwarf mutant interactions in maize

Abstract: SummaryPhytohormone biosynthesis produces metabolites with profound effects on plant growth and development. Modulation of hormone levels during developmental events, in response to the environment, by genetic polymorphism, or by chemical application, can reveal the plant processes most responsive to a phytohormone.Applications of chemical inhibitors and subsequent measurements of specific phytohormones can determine whether, and which, phytohormone is affected by a molecule. In many cases, the sensitivity of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
5
11
0
Order By: Relevance
“…Classic experiments in Vicia faba showed that auxin produced in the shoot apex inhibits axillary meristems[38], and more recently strigolactones were identified as graft-transmissible suppressors of branching (reviewed in [39]). Gibberellins also repress shoot branching in Arabidopsis, maize, and rice, with GA-deficient mutants displaying increased branching compared to wild-type controls[4043]. In contrast, cytokinins and brassinosteroids are both positive regulators of branching[4246].…”
Section: Discussionmentioning
confidence: 99%
“…Classic experiments in Vicia faba showed that auxin produced in the shoot apex inhibits axillary meristems[38], and more recently strigolactones were identified as graft-transmissible suppressors of branching (reviewed in [39]). Gibberellins also repress shoot branching in Arabidopsis, maize, and rice, with GA-deficient mutants displaying increased branching compared to wild-type controls[4043]. In contrast, cytokinins and brassinosteroids are both positive regulators of branching[4246].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PPZ-treated plants displayed several phenotypes common to BR-deficient or signaling mutants, including dwarf shoots, short roots, and dark green leaves [18,25,26]. The reduction in growth observed in this study is likely due to reduced endogenous BR levels by PPZ inhibiting the BR biosynthesis enzymes [18,27]. Transcript levels of the BR biosynthesis genes (OsDWF4, OsD2, and OsCYP85A1), which are feedback-regulated by the BR signaling pathway [28], showed significant upregulation (Fig.…”
Section: Effect Of Ppz On Plant Growth Under N and Pi Deficienciesmentioning
confidence: 63%
“…Application of 10 nM BL reverted hypocotyl length to untreated values while 1 µM GA 3 had a minute effect, confirming that BR but not GA biosynthesis is targeted [167]. Inhibition of BR biosynthesis was also observed in A. thaliana and in Zea mais [213,254]. For the latter a strong dependency on the genetic background was observed [254].…”
Section: Inhibitors Of Brassinosteroid Biosynthesismentioning
confidence: 87%
“…Min et al used uniconazole and the structurally similar triazole paclobutrazol, another growth retardant inhibiting GA biosynthesis [213], as lead compounds for identification of specific and potent BR biosynthesis inhibitors [214]. The obtained products were first tested for inhibition of GA biosynthesis using a rice stem elongation assay since it was thought at that time that rice stem elongation depends only on GAs but not on BRs.…”
Section: Inhibitors Of Brassinosteroid Biosynthesismentioning
confidence: 99%